Refractory epilepsy in children with brain tumors. The urgency of neurosurgery - Marília Rosa Abtibol Bernardino; Carolina Funayama; Ana Paula Andrade Hamad; Hélio Machado; Américo Sakamoto; Ursula Thome; Vera Cristina Terra; Antonio Carlos dos Santos (Arquivos de Neuro-Psiquiatria)
ABSTRACT In order to verify indications for surgery, 27 patients with refractory epileptic seizures and brain tumor, aged up to 19 years at the time of surgery, were studied between 1996 and 2013 and followed up for at least one year. The mean interval between the onset of seizures and the diagnosis of the tumor was 3.6 years, and from diagnosis to the surgery, 18 months. The location of the tumor was in the temporal lobe in 16, with ganglioglioma and dysembryoplastic neuroepithelial tumors being the most frequent. Among the patients, 92.5% and 90.4% were seizure-free in the first and fifth year after surgery, respectively. Twelve of 16 children were successful in becoming drug-free, with complete withdrawal by 3.2 years. Surgery proved to be potentially curative and safe in these cases, suggesting that the tumor diagnosis and surgery cannot be postponed.